2019
DOI: 10.1136/vr.104461
|View full text |Cite
|
Sign up to set email alerts
|

Haematological profile in foals during the first year of life

Abstract: Foals’ haematological values change constantly during their first year of life. The use of updated age-based reference intervals (RIs) is imperative for providing accurate diagnosis and optimum care for sick foals. The authors' objective was to provide updated RIs for 13 haematological values in 2, 7, 14, 30, 90, 180 and 365-day-old foals and to investigate the changes over time in each measured value. Venous blood was collected at those ages from clinically healthy foals. Thirteen haematological values were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
9
1
1
Order By: Relevance
“…Hematologic profiles of neonatal foals have been established with no defined reference range for SAA concentration within the first 72 hours of life, a time of risk for sepsis. [39][40][41] In our study, only 5% (4/86) of the healthy foals <24 hours had a SAA concentration >100 μg/mL, whereas 28% (24/86) of the healthy foals >24 < 48 hours had SAA concentration >100 μg/mL.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Hematologic profiles of neonatal foals have been established with no defined reference range for SAA concentration within the first 72 hours of life, a time of risk for sepsis. [39][40][41] In our study, only 5% (4/86) of the healthy foals <24 hours had a SAA concentration >100 μg/mL, whereas 28% (24/86) of the healthy foals >24 < 48 hours had SAA concentration >100 μg/mL.…”
Section: Discussioncontrasting
confidence: 60%
“…A SAA reference range in neonatal foals has not been established, but clinicians use the degree of increase to describe the magnitude of the change as mild, moderate, or marked, but this categorization is subjective. Hematologic profiles of neonatal foals have been established with no defined reference range for SAA concentration within the first 72 hours of life, a time of risk for sepsis 39‐41 . In our study, only 5% (4/86) of the healthy foals <24 hours had a SAA concentration >100 μg/mL, whereas 28% (24/86) of the healthy foals >24 < 48 hours had SAA concentration >100 μg/mL.…”
Section: Discussionmentioning
confidence: 58%
“…[34][35][36] BUN was low in some foals likely due to high anabolic rate and nursing. [32][33][34]39 Alkaline phosphatase was increased outside the reference range in 1-3-month-old foals. It is normal for alkaline phosphatase activity to be high in the first several weeks of life but can be increased for up 90 days after birth therefore it is typically not a good indicator of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should be designed to determine if growth and age Another limitation of this study that deserves special attention is that it did not assess the potential for liver toxicity of repeated acetaminophen administration since it was a single-dose study, nor were liver biopsies performed. Acetaminophen-induced liver toxicity is a significant adverse effect in humans 14,33,34 but has not been seen in horses to this date. Importantly, the extent of the liver injury may impair acetaminophen metabolism and prolong the half-life, which can contribute to further liver damage and alter drug disposition.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to understand that young and adults are physiologically different, which justifies the need to obtain age-specific reference intervals. Several studies have indicated significant differences between the physiology of young and adult cattle [ 17 , 18 , 19 , 20 , 21 ], and the same can be found for other species such as horses [ 22 ], dogs [ 23 , 24 ] and pigs [ 25 ]. Some studies showed significant differences also in the hematological and biochemical profiles of growing dromedary calves from birth to the 4th week of age [ 26 ], and between young and adult [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 95%